Apolipoprotein E gene and age-related macular degeneration in a Chinese population - Sun, Erdan (Molecular Vision, 2011)
PURPOSE: To examine the association between apolipoprotein E (APOE) polymorphisms and age-related macular degeneration (AMD) in a Chinese population. METHODS: The study consisted of 712 subjects, including 201 controls, 363 cases with early AMD, and 148 cases with exudative AMD. Genomic DNA was extracted from venous blood leukocytes. Common allelic variants of APOE (ε2, ε3, and ε4) were analyzed by PCR and direct sequencing. RESULTS: APOE ε3ε3 was the most frequent genotype, with a frequency of 72.6% in controls, 72.5% in early AMD, and 70.3% in exudative AMD. Frequency of the ε2 allele was 6.7% in controls, 7.4% in early AMD, and 8.8% in exudative AMD. Frequency of the ε4 allele was 8.7% in controls, 7.7% in early AMD, and 7.8% in exudative AMD. No statistically significant difference in APOE genotype and allele frequency distribution was observed among controls, cases with early AMD, and cases with exudative AMD. For ε2 allele carriers, the odds ratio was 1.12 (95% confidence interval [CI], 0.65–1.93) for early AMD and 1.06 (95% CI, 0.53–2.10) for exudative AMD. For ε4 allele carriers, the odds ratio was 1.04 (95% CI, 0.61–1.75) for early AMD and 0.83 (95% CI, 0.42–1.62) for exudative AMD. CONCLUSIONS: Our data provide no evidence to support an association of APOE polymorphisms with early or exudative AMD, suggesting that APOE is less likely to be a major AMD susceptibility gene in the Chinese population.